The effects of rain fade on millimetre wave channel in tropical climate - Asma Ali Budalal; Islam Md Rafiqul; Mohamed Hadi Habaebi; Tharek Abd. Rahman (Bulletin of Electrical Engineering and Informatics, 2019)
The main objective of this paper to determine multipath and time-varying channel behaviour of short-terrestrial millimetre-wave point-to-point radio links. In an attempt to invigorate the impact of rain attenuation on mm-wave channel parameters such as the RMS delay spread, path loss received power strength and Rician distribution with a K factor. A brief analysis of rain fading was presented based on the simultaneous measurement of one-minute rain rate and its effects on a short experimental link of 38 GHz. Rain fade average is observed as high as 16 dB for 300 m path at about 125 mm/hr rain intensity. The statistical spatial channel mode (SSCM) simulation software was utilized for an operating frequency of 38 GHz. To generate of power delay profile (PDP). For both omnidirectional and directional antenna. The RMS delay spread and path loss has been estimated using the environmental parameters of Kuala Lumpur city which illustrates the theoretical performances of 5G in Malaysia. It is observed that RMS delay spread, path loss received power strength and K factor effected dramatically by rain fade. (SSCM) simulation software has to be modified to consider rain fade dynamic characteristics to achieve ultra-reliability requirements of outdoor applications in the tropical regions. This study is important for understanding signal propagation phenomena in short distance and enabling the utilization of the millimetre wave band for an urban micro-cellular environment for 5G communication system.